A GABBR2 gene variant modifies pathophysiology in Huntington's disease. (4th May 2016) - Philpott, April L.; Fitzgerald, Paul B.; Bailey, Neil W.; Churchyard, Andrew; Georgiou-Karistianis, Nellie; Cummins, Tarrant D.R.
Graphical abstract: Highlights: Genetic modifiers of pathophysiology in HD have not been previously investigated. SNP mapping of GABA and dopamine receptor genes was performed in 29HD participants. A putatively functional GABBR2 variant was associated with cortical excitability. GABBR2, GABRA2 and DRD2 SNPs were associated with pathophysiology and age at onset. Uncovering genetic modifiers helps to identify novel targets for clinical trials. Abstract: Striatal degeneration in Huntington's disease (HD) causes changes in cortico-subcortical pathways. Transcranial magnetic stimulation (TMS) is a valuable tool for assessing pathophysiology within these pathways, yet has had limited application in HD. As cortico-subcortical pathways are largely mediated by GABA and dopamine receptor genes, understanding how these genes modulate neurophysiology in HD may provide new insights into how underlying pathology maps onto clinical phenotype. Twenty-nine participants with HD underwent motor cortex stimulation, while corticospinal excitability, cortical inhibition and intracortical facilitation were indexed via peripheral electromyography. Single-nucleotide polymorphism mapping was performed across six genes that are known to modulate cortico-subcortical pathways ( GABRA2, GABBR1, GABBR2, DRD1, DRD2, DRD4 ). Genetic associations with six TMS measures and age at onset were investigated. Our hierarchical multiple regression analysis, controlling for CAG and age, revealed that a GABBR2 variant, predicted to be disease-causative, was significantly associated with corticospinal excitability at corrected levels. A subsequent uncorrected exploratory analysis revealed associations between GABBR2, GABRA2 and DRD2 variants with TMS measures of corticospinal excitability and cortical inhibition in HD, as well as with age at onset. Our findings support the notion that uncovering genetic associations with pathophysiological measures and age at onset is an important way forward in terms of generating meaningful biomarkers with diagnostic and prognostic sensitivity, and identifying novel human-validated targets for future clinical trials.